1961
DOI: 10.1126/science.133.3463.1489
|View full text |Cite
|
Sign up to set email alerts
|

Nature of "Sex-ratio" Agent in Drosophila

Abstract: Several lines of evidence implicate small spirochetes, presumably treponemata, as etiologic agents in the production of the maternally transmitted "sex ratio" condition (SR) in Drosophila nebulosa, in D. willistoni, and in strains of D. melanogaster into which the SR condition has been artificially transferred. The presence of treponemata in the hemolymph of adult females of these species is completely correlated with the production of unisexual progenies and like this condition is dependent on the genotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

1962
1962
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(42 citation statements)
references
References 6 publications
0
41
0
1
Order By: Relevance
“…1), the differences in spiroplasma densities between the fly strains may be attributable to the host genotype rather than to the symbiont genotype, although the possibility cannot be ruled out that slight genetic differences between the symbionts somehow affected the observed differences in bacterial density. Note that the G87 insect is the native host for the spiroplasma, while the ORNSRO insect is the nonnative host generated by transfection with the spiroplasma from a different source (36,37). Thus, it is conceivable that the infection densities of the spiroplasma might be negatively affected in the nonnative host ORNSRO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), the differences in spiroplasma densities between the fly strains may be attributable to the host genotype rather than to the symbiont genotype, although the possibility cannot be ruled out that slight genetic differences between the symbionts somehow affected the observed differences in bacterial density. Note that the G87 insect is the native host for the spiroplasma, while the ORNSRO insect is the nonnative host generated by transfection with the spiroplasma from a different source (36,37). Thus, it is conceivable that the infection densities of the spiroplasma might be negatively affected in the nonnative host ORNSRO.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1960s, an Oregon-R strain of D. melanogaster, which had initially been free of spiroplasma infection, was injected with hemolymph of the tropical drosophilid fly D. nebulosa that harbored the male-killing spiroplasma NSRO. The transfected fly strain exhibited a strong male-killing phenotype and has been maintained in the laboratory for over 40 years (36,37). In 2000, hemolymph of adult females of the fly strain was injected into a fresh, uninfected Oregon-R strain of D. melanogaster, whereby an isofemale strain, named ORNSRO, was established and has been maintained in our laboratory (1).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the ability of these organisms to multiply prolifically in both ticks and insects (9,11,15,161, their association with arthropods is doubtless more extensive than heretofore realized.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 5, a list of sensitive chromosomes is presented. It has been found that some extrachromosomal elements in animals are symbiotic microorganisms; e. g, sigma virus responsible for CO2 sensitivity trait in Drosophila melanogaster (reviewed by L'Heritier 1958), certain spirochetes responsible for "sexratio" conditions in several species of Drosophila (Poulson and Sakaguchi 1961;Poulson 1968) or bacteria responsible for the killing trait in Paramecium (Beale and Juland 1969). Although it appears to be early to argue the entity of delta, the problem is outlined below based on the results obtained so far.…”
Section: Discussionmentioning
confidence: 99%